Legends of Lotus Island : The Guardian Test - Book 1 - Soontornvat, Christina (New York : Scholastic Press, 2023)
From two-time Newbery honor recipient Christina Soontornvat comes a compelling new young middle grade fantasy series for readers who love stories about animals, magic, and kids like them embracing their power to change the world.
Keywords: Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Fiction; Friendship -- Fiction; Magic -- Fiction; Juvenile fiction